dSPACE Validation of Improved Backstepping Optimal Energy Control for Photovoltaic Systems - N. Benbaha; F. Zidani; MS. Nait-Said; S. Zouzou; S. Boukebbous; H. Ammar (6th International Renewable and Sustainable Energy Conference (IRSEC), 2018)
In this paper, an efficient and fast MPPT power control of photovoltaic systems based on backstepping approach is presented. The proposed control scheme consists of two cascade loops; in the first loop, the auto-scaling variable step-size perturb and observe MPPT technique estimates the reference voltage of all electrical load values. The robust backstepping controller has been adopted to remove steady state oscillations in the second loop. Further, the performance of proposed control system has been analyzed through dSPACE DS-1104 experimental validation with Isofoton photovoltaic module under real climatic conditions at Biskra (Algeria) region. The results obtained by the used controller averred a good improvement.